Write an explicit formula for the sequence left-brace a subscript n baseline right-brace equals left-brace negative 3 comma negative Start Fraction 1 over 2 End Fraction comma 2 comma Start Fraction 9 over 2 End Fraction comma 7 comma ellipsis right-brace. Then find a subscript 17.

(1 point)
Responses

a subscript n baseline equals Start Fraction 5 over 2 End Fraction n minus Start Fraction 11 over 2 End Fraction semicolon 37
Image with alt text: a subscript n baseline equals Start Fraction 5 over 2 End Fraction n minus Start Fraction 11 over 2 End Fraction semicolon 37

a subscript n baseline equals Start Fraction 3 over 2 End Fraction n minus Start Fraction 9 over 2 End Fraction semicolon 21
Image with alt text: a subscript n baseline equals Start Fraction 3 over 2 End Fraction n minus Start Fraction 9 over 2 End Fraction semicolon 21

a subscript n baseline equals Start Fraction 5 over 2 End Fraction n minus Start Fraction 11 over 2 End Fraction semicolon Start Fraction 69 over 2 End Fraction
Image with alt text: a subscript n baseline equals Start Fraction 5 over 2 End Fraction n minus Start Fraction 11 over 2 End Fraction semicolon Start Fraction 69 over 2 End Fraction

a subscript n baseline equals negative Start Fraction 5 over 2 End Fraction n plus Start Fraction 11 over 2 End Fraction semicolon negative 37

1 answer

To determine the explicit formula for the sequence \( { a_n } = {-3, -\frac{1}{2}, 2, \frac{9}{2}, 7, \ldots} \), we first examine the pattern in the sequence values.

  1. Finding the First Differences: Let's calculate the differences between consecutive terms:

    • \( -\frac{1}{2} - (-3) = 2.5 \)
    • \( 2 - (-\frac{1}{2}) = 2.5 \)
    • \( \frac{9}{2} - 2 = 2.5 \)
    • \( 7 - \frac{9}{2} = 2.5 \)

    The first differences are constant (all equal to \( 2.5 \)), indicating that the sequence is linear.

  2. Finding the General Form: A linear sequence can be expressed in the form: \[ a_n = mn + b \] where \( m \) is the common difference and \( b \) is the first term of the sequence adjusted based on the index.

    We already found that the common difference \( m = \frac{5}{2} \) because the difference is \( 2.5 \).

  3. Finding the Explicit Formula: We can find \( b \) using the first term:

    • At \( n = 1 \), \( a_1 = -3 \): \[ a_1 = m \cdot 1 + b = \frac{5}{2} \cdot 1 + b = -3 \implies b = -3 - \frac{5}{2} = -\frac{6}{2} - \frac{5}{2} = -\frac{11}{2} \]

    Now, our explicit formula for the sequence is: \[ a_n = \frac{5}{2}n - \frac{11}{2} \]

  4. Finding \( a_{17} \): Now, we calculate \( a_{17} \): \[ a_{17} = \frac{5}{2} \cdot 17 - \frac{11}{2} = \frac{85}{2} - \frac{11}{2} = \frac{74}{2} = 37 \]

Therefore, the explicit formula is: \[ a_n = \frac{5}{2}n - \frac{11}{2} \] and the value of \( a_{17} \) is: \[ \boxed{37} \]